Aplikasi Teori Kendali Pada Permainan Dinamis Non-Kooperatif Waktu tak Berhingga - Nilwan Andiraja (UIN Sultan Syarif Kasim Riau, 2012)
In this paper discuss about application the control theory to form control vector in linier quadratic non-cooperative dynamic game two-player with Nash strategy for infinite time. Discuss was started from general equation for optimal control of continuous time, then discuss to continue to general equation for non-cooperative dynamic game N player for finite time with several assumption. Then, with the same assumption to made general equation for non-cooperative dynamic game two-player for infinite time, which consisting of differential equation dynamical system and objective function suitably. Moreover, with used control theory to form algebraic Riccati equation suitably with differential equation and objective function for each player. Based on algebraic Riccati equation was formed, gotten solution which used to form control vector suitably for each player. Finally gets to be concluded there are exists control vector in linear quadratic non-cooperative dynamic game two-player with Nash strategy for infinite time.Keywords: non-cooperative dynamic game, algebraic Riccati, control vector